The Teaching of Italian Grammar to the Beginner Foreign University Students: a Longitudinal Analysis - Favata, Giovanni (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
In this paper we want to analyse written productions of university students, collected in different academic years by the researcher during his Italian as a second language courses. We will conduct a longitudinal analysis during which we will have a twofold purpose: to monitor the effects of the grammar teaching and to observe the autonomous development of the learners’ interlanguage. For our studies, we will use data coming from a control group, composed by Italian speakers, students at Polytechnic of Turin.